(a+b+c)^3=? how to solve this identity
Answers
Answered by
64
Answer:
• (a+b+c)³=(a³+3a²b+3ab²+b³)+3(a²+2ab+b²)c+3(a+b)c2+c³
•(a+b+c)³=a³+b³+c³+3a²b+3a²c+3ab²+3b²c+3ac²+3bc²+6abc
•(a+b+c)³=(a³+b³+c³)+(3a²b+3a²c+3abc)+(3ab²+3b²c+3abc)+(3ac²+3bc²+3abc)−3abc
•(a+b+c)³=(a³+b³+c³)+3a(ab+ac+bc)+3b(ab+bc+ac)+3c(ac+bc+ab)−3abc
•(a+b+c)³=(a³+b³+c³)+3(a+b+c)(ab+ac+bc)−3abc
•(a+b+c)³=(a³+b³+c³)+3[(a+b+c)(ab+ac+bc)−abc]
I Hope it helps you!
Similar questions
Computer Science,
2 months ago
English,
2 months ago
Math,
2 months ago
Math,
3 months ago
Math,
3 months ago
Computer Science,
11 months ago
Math,
11 months ago